Integrated truth and existential phenomenology : a Thomistic response to iconic anti-realists in science - Trundle, Robert C., 1943- (Value Inquiry Book Series, 2015)
Integrated Truth and Existential Phenomenology: A Thomistic Response to Iconic Anti-Realists in Science relates an existential phenomenology to modal reasoning. By this reasoning, rooted in a consciousness of phenomena in themselves, a Thomistic realism is advanced wherein scientific inquiry yields objective truth and presupposes a causal principle. This principle, as an inferably true modality, strictly implies a first cause. And this cause as a supreme norm, causally created human nature as it ought to be. So with no naturalistic fallacy, a naturalistic ethics is inferred from our psycho-biological nature that also informs art and politics. Politics, as the institutionalization of ethics, is inferable from ethical prescriptions that are as certifiably true as the descriptions of science that inform it.